E REVIEW: DEVELOPMENTS IN ANIMAL GENETIC ENGINEERING AND ANIMAL DNA REPLICATION - Dirga Anugrah Mokoginta; Sekar Ayu Kedaton; Aulia Nisfatuzzahra; Beatrix Magdalena Ottay; Deya Arisca Tuina; Beby Triana Arafah Z. Muis (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
DNA (Deoxyribonucleic Acid) is the primary genetic material responsible for heredity, regulation of cellular activities, and protein synthesis through DNA replication and gene expression. This study aims to review the roles of DNA, DNA replication, and gene expression in supporting the success of animal genetic engineering. The method employed was a literature review of national and international scientific publications from 2016 to 2023 obtained through Google Scholar using keywords related to genetic engineering, animal biotechnology, and DNA replication. The results indicate that recombinant DNA technology and transgenesis have successfully improved productivity, product quality, and disease resistance in animals, such as transgenic fish expressing growth hormone genes and transgenic goats overexpressing antithrombin III (ATIII). DNA replication ensures the stability of modified genetic traits, while gene expression determines the successful production of functional proteins. However, the application of animal genetic engineering requires careful consideration of biosafety, ethics, animal welfare, and environmental impacts. Overall, a comprehensive understanding of DNA molecular mechanisms supports the sustainable development of animal biotechnology.